Performance Analysis of IMC Module in OTE DT100 VHF Radio Based on Required Communication Performance Standards - Lukman Yudand Hidayat; Dian Anggraini; Toni (Politeknik Penerbangan Indonesia Curug, 2026)
Communication between Air Traffic Controllers and pilots is essential to ensure flight safety and operational efficiency. Very High Frequency (VHF) communication systems support reliable air-to-ground communication, with the Interface and Management Card (IMC) module responsible for managing automatic change-over between main and standby transmitters. This study evaluates the performance of the IMC module in relation to Required Communication Performance (RCP) standards and examines the impact of IMC failure on communication continuity and availability. The research employed a mixed-method approach, combining field observations during On-the-Job Training at Minangkabau International Airport, interviews with technicians, and analysis of equipment failure records. Qualitative data were analyzed using thematic analysis, while quantitative evaluation focused on system downtime and response time. The results show that IMC malfunction significantly reduces system continuity and availability, potentially compromising compliance with RCP 10 and RCP 60 requirements. Recommendations are proposed to improve IMC reliability and preventive maintenance practices.